Transformasi Peran Pengawas dalam Upaya Peningkatan Mutu Pendidikan Sekolah: Sebuah Kajian Literatur - Nur Halimah; Silvia Megawati; Abdul Fatah; Noor Eleena Nordin; Agus Mulyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The transformation of the school supervisor’s role has become a strategic necessity in enhancing the quality of education in an increasingly dynamic global era. Supervisors now serve not only as administrators but also as facilitators, motivators, and catalysts for change to promote innovative learning and sustainable professional development. This study employs a qualitative descriptive method with document analysis to examine the evolution of the supervisor's role, challenges encountered, implementation strategies, and their impact on education quality. Findings reveal that the shift from conventional approaches to transformative supervision significantly improves learning quality, strengthens the culture of school excellence, and accelerates the achievement of national education standards (SNP). Challenges such as digital divides, resource limitations, and resistance to change can be addressed through need-based supervision, blended supervision, and multi-stakeholder collaboration. Technology-based approaches have also proven effective in supporting development, particularly in remote areas. The study concludes that transforming school supervisors is a critical element in achieving more inclusive, adaptive, and globally competitive education. Comprehensive policy support, capacity building through technology-based training, and cross-sector collaboration are essential to ensure the sustainability of this transformation.